Archosauromorph remains from the Tarjados Formation (Early-Middle Triassic, NW Argentina) - Ezcurra, Martin Daniel (2015)
The Agua de la Peña Group of the Ischigualasto-Villa Unión Basin (northwestern Argentina) documents the evolution of archosauromorph assemblages in western Gondwana during the late Middle and Late Triassic. However, the South American archosauromorph record in the aftermath of the Permo/Triassic mass extinction (Early–early Middle Triassic) is remarkably scarce and restricted to isolated bones. Here, we describe a recently collected isolated second sacral vertebra and rib that represents one of the few fossils known from the Lower–Middle Triassic Tarjados Formation, the unit that underlies the Agua de la Peña Group. This specimen is identified as an archosauromorph because of the presence of a non-notochordal vertebra and a bifurcated distal end of the second sacral rib. A quantitative phylogenetic analysis places the new specimen as an archosauromorph more derived than protorosaurs. In particular, this specimen resembles Pamelaria, Prolacerta and early rhynchosaurs in the presence of a squared posterior projection of the bifurcated second sacral rib. The new specimen represents the first body fossil of a diapsid formally described in the Tarjados Formation and the oldest member of the group in the Ischigualasto-Villa Unión Basin. As a result, this specimen increases the high-level taxonomic richness of Archosauromorpha in South America in the aftermath of the Permo/ Triassic mass extinction.